Growth and poverty in rural China: the role of public investments - Fan, Shenggen; Zhang, Linxiu; Zhang, Xiaobo (International Food Policy Research Institute, 2000)
Public investment, together with institutional and policy reforms, has contributed substantially to rapid economic growth in rural China since the late 1970s. This rapid growth has also led to dramatic reductions in rural poverty. In this study we use a simultaneous equations model and time-series (1978-97), cross-sectional (25 provinces) data to analyze the differential impact of different types of public investments on growth and poverty reduction in rural China. The results show that government expenditures on education have by far the largest impact on poverty reduction, and the second largest impact on production growth; it is a dominant “win-win” strategy. Government spending on agricultural research and extension has the largest impact on agricultural growth, and the third largest impact on poverty reduction. It is another win-win strategy. The next best investment is rural telecommunications, which gives the second largest impact on poverty reduction and the third largest impact on agricultural growth. The results also show that there are regional tradeoffs in achieving growth and poverty alleviation goals. If the government wishes to maximize its poverty reduction effects, then investments should be targeted to the western region. However, the sacrifice in growth by investing more in the western region is small. But, the government wishes to maximize the returns to growth in agricultural production, then it should definitely target the central region.